THE INFLUENCE OF TOTAL QUALITY MANAGEMENT ON STAR HOTEL PERFORMANCE - M.P, Dr. Sunil; G, Dr. Suresh; H, Dr. Shobharani (The journal of contemporary issues in business and government, 2021)
The tourism and travel industry in India is growing at a drastic pace and is having a countable contribution to the GDP. The Foreign Tourists Arrival to India has increased by 23.77% since last 5 years yet in Karnataka state there is a downtrend in Tourist Visit. The major components of tourism and travel industry includes destination, food and accommodation, guides and brokers etc. and among them food and accommodation is provided by hotels which is a vital influencing factor in comforting the tourists away from nest and plays a leading role in boosting the tourist traffic to the destination. Therefore it pinches the question on to what extent the star hotels are providing quality services and how hotels are performing to support the tourism and travel industry. Hence the study focused on empirically investigate implementation of Total Quality Management which is the most used quality management technique for providing quality services among the star hotel and its impact on hotel performance. The sample of star hotels was selected through tippet random sampling technique and the data was collected through structured TQM questionnaire which were distributed to hoteliers and employees. The hypothesis was tested with SEM analysis and the elements of TQM practices showed a positive relationship with key performance indicators of star hotels. Further the present study suggests the importance of proper planning and communicating as priority before starting TQM implementation, opting the right leadership style and consistency in innovation and management for reaping the benefits of TQM and improving hotel performance.